Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13104-019-4072-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-care related knowledge, attitude, practice and associated factors among patients with diabetes in Ayder Comprehensive Specialized Hospital, North Ethiopia

Abstract: ObjectiveA good self-care practice is important for patients with diabetes to achieve the desired treatment targets and to contribute meaningfully in the management of their disease. The study aimed to assess the level of knowledge, attitude and practice of diabetes self-care and to identify the factors associated with diabetes self-care.ResultsA total of 338 patients with diabetes having mean age of 45.8 years were included in the study. Among those 70.4%, 70.4% and 25.5% of the patients had a good knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
40
8
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 15 publications
20
40
8
6
Order By: Relevance
“…Similar to studies in Ethiopia [13,23] and Dhaka [25], our study found signi cant associations between diabetes-related knowledge with levels of education, marital status, occupation, and duration of the disease. However, contrary to our study, males have a better knowledge of the disease than females in India [38] and Zimbabwe [39].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to studies in Ethiopia [13,23] and Dhaka [25], our study found signi cant associations between diabetes-related knowledge with levels of education, marital status, occupation, and duration of the disease. However, contrary to our study, males have a better knowledge of the disease than females in India [38] and Zimbabwe [39].…”
Section: Discussionsupporting
confidence: 88%
“…Southern Nations Nationalities and Peoples (SNNPs) (10,32), Tigray (33,34), and Addis Abeba (8,35) each contributed two articles to the review. While the remaining study was from Benishangul Gumuz region (36).…”
Section: Characteristics Of Included Primary Studiesmentioning
confidence: 99%
“…Furthermore, the relationship between diabetic's self-care practice and residence of DM patients was reviewed by five articles. All studies (25,28,29,33,36) demonstrate that being an urban residence promoted diabetic self-care practice. The effect size of the residence revealed that living in an urban area has a threefold chance of practicing diabetics self-care than DM patients residing in the rural area 3.26(2.24, 4.74), I 2 =96.3%, P<0.001) (Figure9).…”
Section: Determinants Of Diabetics' Self-care Practicementioning
confidence: 99%
“…Southern Nations Nationalities and Peoples (SNNPs) (10, 32), Tigray (33,34), and Addis Abeba (8,35) each contributed two articles to the review. While the remaining study was from Benishangul Gumuz region (36).…”
Section: Characteristics Of Included Primary Studiesmentioning
confidence: 99%
“…Furthermore, the relationship between diabetic's self-care practice and residence of DM patients was reviewed by five articles. All studies (25,28,29,33,36)…”
Section: Determinants Of Diabetics' Self-care Practicementioning
confidence: 99%